Systematic placement and identity of Eumicrus deplanatus L.W. Schaufuss (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2020)
Examination of the type specimen of the Neotropical Eumicrus deplanatus Schaufuss, as well as material newly collected in Venezuela, allowed for clarifying the systematic placement of this enigmatic species. It is not a member of Scydmaenus Latreille or Euconnus Thomson, genera in which it was placed by previous authors, but belongs in Sciacharis Broun. Sciacharis (Palaeoconnus) deplanatus comb. n. is established, and the species is redescribed. For the first time males are reported, and the aedeagus, crucial for species identification, is illustrated.